New approaches in teaching laser engineering classes - modeling and building up a laser - Alexeev, Ilya; Pflaum, Christoph; Schmidt, Michael (SPIE-INT SOC OPTICAL ENGINEERING, PO BOX 10, BELLINGHAM, WA 98227-0010 USA, 2017)
We present a simulation tool to model performance of a bulk solid state laser and propose several ways how this tool can be used to enhance educational experience of the student studying laser technology. In one of the possible approaches, the ASLD software can complement available educational laser kits to provide the students with more universal practical training. In the second approach, which is the primary focus of this contribution, the ASLD software can be used as a development tool that allows students to verify their understanding of the subject as well as to propose and verify their own design ideas. The software can be extremely helpful if an experimantal setup has to be built from already present optical components in order to reduce the cost of training or if specific design objectives have to be attained.
Keywords: Laser resonator modeling; ASLD software; ultrafast lasers